KNOWLEDGE SOCIETY AND POST-NONCLASSICAL SCIENCE: INTERACTION CONTEXTS - Броннікова, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article discusses the changes in science against the backdrop of the social transformations of the early 21st century. Modern development of science called postnonclassical features of the modern scientific production is interdisciplinary.